1085. Epidemiology and Outcomes of Histoplasmosis in Transplant Recipients. (31st December 2020) - Rutjanawech, Sasinuch; Larson, Lindsey; Franklin, Alexander; Hendrix, Michael Joshua; Powderly, William; Spec, Andrej
Abstract: Background: Histoplasmosis in transplant recipients is understudied. We reviewed a large cohort of histoplasmosis in patients with solid organ and stem cell transplants in an endemic area to describe the epidemiology, clinical findings and outcomes. Methods: We performed a single-center retrospective cohort study of patients diagnosed with histoplasmosis between 2002 and 2017. Demographic data, clinical findings, diagnostic methods, treatment, and mortality were collected. We compared the characteristics of patients with history of transplant to non-transplant (NT) patients. Results: We identified 261 patients with histoplasmosis. Of those, 28(11%) were transplant recipients; 8(29%) liver, 8(29%) lung, 6(21%) kidney, 3(11%) heart, and 3(11%) stem cell. Median time from symptom onset to diagnosis was 6 vs 34 days in transplant vs NT groups (p=0.001). Lung was the most common organ involvement (89% in transplants vs 78% in NT, p=0.168). Spleen involvement was more commonly found in transplant patients (29 vs 14%, p=0.039). In patients with disseminated disease, urine antigen was 100% sensitive in transplant patients compared to 78% in the NT group (p=0.038). Duration of treatment was 13 vs 6 months in transplant vs NT patients (p= 0.003). Mortality was comparable between groups (14 vs 15% in transplant vs NT, p=0.918). Median time from transplant to diagnosis was 4.21 years. However, five patients (18%) developed histoplasmosis within 6 months. For these early diagnosed patients, ICU admission rate was 80 vs 30% (p=0.04) and rate of mechanical ventilator use was 80 vs 22% (p=0.011) compared to patients diagnosed later. Table 1: Patient characteristics Table 2: Organ involvement Table 3: Diagnostic test positivity Conclusion: Transplant recipients with histoplasmosis are likely to be diagnosed early and be treated longer. Urine antigen is highly sensitive for diagnosis of disseminated disease. Histoplasmosis that occurs within the first 6 months after transplantation tends to be more severe. Disclosures: Andrej Spec, MD, MSCI, Astellas (Grant/Research Support)Mayne (Consultant)Scynexis (Consultant)